Inactivation of nuclear histone deacetylases by EP300 disrupts the MiCEE complex in idiopathic pulmonary fibrosis - Rubio Nava, Karla Maria; Singh, Indrabahadur; Cordero, Julio; Dobreva, Gergana; Heikenwälder, Mathias (Nature Communications, 2019)
Idiopathic pulmonary fibrosis (IPF) is a lethal disease with insufficient treatment strategies. Here the authors show that reduction of the microRNA MIRLET7D and hyperactivation of EP300 contribute to impaired epigenetic silencing by the MiCEE complex in pulmonary fibroblasts of IPF patients, and demonstrate the benefit of inhibiting EP300 for the treatment of IPF.
Gesehen am 27.01.2020